THE TERREIRO KITCHEN AS A TERRITORY OF CONSTRUCTION AND IDENTITY AFFIRMATION - Pinheiro Lima, Luiz Fabio (2024)
This article seeks to produce an anthropological look focused on kafubera, that is, the Terreiro cuisine. During ethnographic field research, I established a dialogue between my experiences as a researcher and an initiate of Candomblé de Angola, so that, in this way, I could develop a discourse emphasizing the Terreiro cuisine as a territory of identity construction and affirmation. The anthropological literature on the subject, together with the observations and interpretative analyzes among the research subjects, of which I include myself, were the bases for the investigations. The analyzes start from the observation of the rites that involve eating practices and Candomblé followers, also highlighting the common activities of everyday life, responsible for the production of extensions of identities and the circulation of teachings within the Terreiro. I conclude that food practices related to the kitchen in Candomblé, through the production of food and other ways of eating in Terreiro, reveal knowledge, conduct and learning that are responsible for the process of identity formation of Santo's sons and daughters.